2017
DOI: 10.1017/s0954394517000096
|View full text |Cite
|
Sign up to set email alerts
|

There's three variants: Agreement variation in existentialthereconstructions

Abstract: Previous studies of agreement variation in existential there constructions treat the variable as binary, distinguishing between agreeing and nonagreeing variants. Using new data from a corpus of English spoken in California, we argue that this widely studied variable cannot be fully understood without instead making a three-way distinction between agreement (there are/were + plural), nonagreement using a full form of the verb (there is/was + plural), and nonagreement using there's. We motivate this three-way d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 17 publications
1
11
0
Order By: Relevance
“…Apparent‐time analyses of spoken English reveal a similar trend. Britain and Sudbury () found that, in two geographically distant varieties of English, younger speakers were more likely than older speakers to use nonagreeing forms of the construction, and Krejci and Hilton () found that it is the form there's alone which is driving this age correlation (Figure ). For speakers under the age of 35, there's is the preferred form for introducing plural nouns by a wide margin.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Apparent‐time analyses of spoken English reveal a similar trend. Britain and Sudbury () found that, in two geographically distant varieties of English, younger speakers were more likely than older speakers to use nonagreeing forms of the construction, and Krejci and Hilton () found that it is the form there's alone which is driving this age correlation (Figure ). For speakers under the age of 35, there's is the preferred form for introducing plural nouns by a wide margin.…”
Section: Introductionmentioning
confidence: 99%
“…Rate at which speakers across three age groups use agreeing and nonagreeing variants of the existential construction to introduce plural nouns (Krejci and Hilton : 193)…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations